The maternal-to-zygotic transition in bovine in vitro-fertilized embryos is associated with marked changes in small non-coding RNAs. Issue 2 (25th August 2018) - Cuthbert, Jocelyn M; Russell, Stewart J; White, Kenneth L; Benninghoff, Abby D
Abstract: In mammals, small non-coding RNAs (sncRNAs) have been reported to be important during early embryo development. However, a comprehensive assessment of the inventory of sncRNAs during the maternal-to-zygotic transition (MZT) has not been performed in an animal model that better represents the sncRNA biogenesis pathway in human oocytes and embryos. The objective of this study was to examine dynamic changes in expression of sncRNAs during the MZT in bovine embryos produced by in vitro fertilization (IVF), which occurs at the 8-cell stage. An unbiased, discovery-based approach was employed using small RNAseq to profile sncRNAs in bovine oocytes, 8-cell stage embryos and blastocyst stage embryos followed by network and ontology analyses to explore the functional relevance of differentially expressed micro-RNAS (miRNAs). The relative abundance of miRNAs was markedly higher in 8-cell stage embryos compared to oocytes or blastocyst stage embryos. This shift in miRNA population was largely associated with upregulation of miRNAs predicted to target genes involved in the biological processes of cell development, cell division, Wnt signaling, and pluripotency, among others. Distinct populations of piwi-interacting-like RNAs (pilRNAs) were identified in bovine oocytes and blastocyst stage embryos, though pilRNAs were nearly absent in 8-cell stage embryos. Also, small nucleolar RNAs were highly expressed in 8-cell stage embryos. Overall, these data reveal a strong dynamic shift in the relative abundance of sncRNAs associated with the MZT in bovine oocytes and embryos, suggesting that these molecules may play important roles in the shift from maternal to zygotic control of gene expression. Abstract : In bovine oocytes and IVF embryos, the maternal-to-zygotic transition is associated with a marked shift in abundance of specific sncRNA classes, including miRNAs, pilRNAs, and snoRNAs.